The influence of saccharin on the electrodeposition and properties of Co–Ni alloy thin films. (July 2015) - Tebbakh, S.; Messaoudi, Y.; Azizi, A.; Fenineche, N.; Schmerber, G.; Dinia, A.
Abstract : Co–Ni alloys thin films were electrodeposited on Ru substrates from a chloride-saccharin bath at pH 3.8 and the effects of adding saccharin to the bath on the electrochemical deposition, corrosion resistance, chemical composition, physical and magnetic properties of the deposits were investigated. The analytical techniques of cyclic voltammetry (CV), potentiodynamic polarisation, electrochemical impedance spectroscopy (EIS), atomic absorption spectroscopy (AAS), atomic force microscopy (AFM), X-ray diffraction and hysteresis curves were applied to assess the codeposition process, and determine corrosion resistance, composition, morphology, nanocrystallinity and magnetic properties. Effectively, CV measurements revealed that the addition of saccharin in the electrolytic bath modifies the deposition process and an anomalous codeposition takes place; this enhanced the Co percentage in the Co–Ni deposits. Saccharin addition also increases the double layer capacitance and decreases the charge transfer resistance. On the other hand, the Tafel plots show a higher corrosion resistance for the deposits obtained from a bath with saccharin than those obtained from a bath without it. Furthermore, the presence of the saccharin in the bath also causes notable changes in the morphology and structure characteristics of deposits. In addition, it was found that the additive influences the magnetic properties of Co–Ni alloy thin films. The coercivity and magnetisation saturation are diminished for Co–Ni films prepared from electrolytes with addition of saccharin.